The Implementation of THIEVES Strategy in Teaching Reading Comprehension of Descriptive Text - Endang Susilawati; Sumarni; Stepanus Rico (Universitas Cokroaminoto Palopo, 2023)
This study aimed to investigate whether the THIEVES strategy is effective or not in teaching reading comprehension of the descriptive text to students in the eighth grade at SMP Negeri 2 Ketungau Tengah, Sintang, Kalimantan Barat. It also investigates how effective it is. This research is a one-group pre-test and post-test design. In this research, the total population is 36 students, 18 from VIII A and 18 from VIII B. The researchers used random cluster sampling to select 18 students from class VIII A as the research sample. The researchers also collected and analyzed pre-test and post-test data using a t-test. The average pre-test score was 52.5, while the average post-test score was 62.5. The result of the t-test was 4,41, as shown by the data. Based on the above data analysis, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted because the t-test was higher than the t- table (4.41>1.740). Therefore, it indicated that the THIEVES strategy is effective in teaching reading comprehension. In addition, the effect size was 1,19, indicating a strong effect (>1.00). In conclusion, implementing the THIEVES strategy in teaching reading comprehension of descriptive text to the eight grade students in the school is highly effective.